45,X[2]/46,X,der(Y).ish Psu idic(Y)(q11.2)[38] mosaic karyotype in mixed gonadal dysgenesis: a case report and literature review - Zhang, Qiang; Chen, Xiaoxiao; Cao, Yanyan; Zhou, Yun; Liu, Yingye; Liu, Lijun; Liu, Lei; Cui, Xiaowei (Frontiers in Pediatrics, 2024)
Mixed gonadal dysgenesis is caused by a variety of chromosome abnormalities, most commonly Y chromosome mosaicism. An 8-year-old boy presented with short stature for possible treatment with recombinant growth hormone. He had a history of mixed gonadal dysgenesis (hypospadias, bilateral cryptorchidism, processus vaginalis and dysplastic immature uterus) and series of corrective surgeries. At 14 months of age, chromosomal karyotyping revealed 46,X,+mar. Upon presentation, lab testing was consistent with the male phenotype at prepuberty. Fluorescence in situ hybridization revealed 45,X[2]/46,X,der(Y).ish psu idic(Y)(q11.2)(SRY++,DYZ3++)[38] karyotype. A literature review identified 8 case reports of mixed gonadal dysgenesis associated with 45,X/46,X,idic(Y)(q11.2). Neither sex phenotype nor short stature correlated with the 46,X,idic(Y)(q11.2) mosaic ratio.